Thin Capitalization Rules and Entrepreneurial Capital Structure Decisions - Alexandra Maßbaum; Caren Sureth (BuR - Business Research, 2009)
Tax planners often choose debt over equity financing. As this has led to increased corporate debt financing, many countries have introduced thin capitalization rules to secure their tax revenues. In a general capital structure model we analyze if thin capitalization rules affect dividend and financing decisions, and whether they can partially explain why corporations receive both debt and equity capital. We model the Belgian, German and Italian rules as examples. We find that the so-called Miller equilibrium and definite financing effects depend significantly on the underlying tax system. Further, our results are useful for the treasury to decide what thin capitalization type to implement.
urn:nbn:de:0009-20-21638
Keywords: 650; Miller equilibrium; business taxation; capital structure; critical income tax rate; financing decision; tax planning; thin capitalization; Kapitalstruktur; Bilanzierungspflicht; Betriebliche Finanzwirtschaft; Unternehmensbesteuerung; Steuerplanung; Belgien; Deutschland; Italien